SISTEM PENDUKUNG KEPUTUSAN STAFFING MANAGEMENT DI PT. INTERNUSA ASRIDAYA SAKTI - Sarmidi -; Yusuf Sumaryana (LPPM STMIK DCI, 2015)
In the process of decision-making objective, effective, fast, precise and accurate in the preparation of an organization's management of the company is not easy, because the decisions are not objective, of course will affect existing systems. Therefore, we need a system that is able to handle decisions objectively in a relatively fast and effective.The system used in the case of staffing management applied in PT. Internusa Asridaya Way, is the essential problem which in essence is one of the capital's success in an organization to achieve its goals - goals that are expected. Therefore, the thesis is structured in order to provide an effective solution initial hypothesis and quickly by using computer systems technology, which can support decision making in the process of staffing management at PT. Internusa Asridaya magic.Keyword: Decision-Making Objective, Staffing Management, PT Internusa Asridaya Magic